Pengaruh Sumber Daya Manusia, Lingkungan, Metode Kerja dan Material terhadap Penerapan Standar Pembangunan Jembatan - nugroho, suko; Mudiyono, Rachmat (UNISSULA Semarang, 2024)
The primary objective of this study is to identify key variables influencing the implementation of bridge construction standards, focusing on human resources, environment, work methods, and materials. Using a quantitative approach, the study involved 130 respondents, including project managers, field engineers, supervisors, construction workers, and supervising consultants. Data were collected through validated questionnaires and analyzed using linear regression to understand the relationships between the tested variables and the implementation of bridge construction standards. The results indicate that all four factors have a significant impact, with materials being the most dominant variable (regression coefficient of 0.49, p-value < 0.05) affecting the effectiveness of standard implementation. Additionally, human resources, environment, and work methods were found to play essential roles in improving construction quality and bridge safety. Effective human resource management, proper material selection, adaptation to environmental conditions, and efficient work methods are crucial to ensure compliance with construction standards. The findings of this study can serve as a reference for developing future construction regulations and policies, although there are limitations related to the scope and variables examined. Further research with a broader scope and additional variables, such as financial and technological aspects, is highly recommended to gain a more comprehensive understanding.